2016
DOI: 10.1080/15384101.2016.1152432
|View full text |Cite
|
Sign up to set email alerts
|

Metformin attenuates transforming growth factor beta (TGF-β) mediated oncogenesis in mesenchymal stem-like/claudin-low triple negative breast cancer

Abstract: Mesenchymal stem-like/claudin-low (MSL/CL) breast cancers are highly aggressive, express low cell-cell adhesion cluster containing claudins (CLDN3/CLDN4/CLDN7) with enrichment of epithelial-to-mesenchymal transition (EMT), immunomodulatory, and transforming growth factor-β (TGF-β) genes. We examined the biological, molecular and prognostic impact of TGF-β upregulation and/or inhibition using in vivo and in vitro methods. Using publically available breast cancer gene expression databases, we show that upregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
67
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 65 publications
1
67
0
Order By: Relevance
“…Epidemiological studies consistently suggest an anti-cancer effect of metformin in individuals with diabetes, including breast cancer (1-3). A number of preclinical studies of mammary carcinogenesis and in vitro studies using breast cancer cell lines are consistent with this assertion of metformin's beneficial effects (4-9). Even so, other preclinical studies of mammary carcinogenic models failed to see any effect of metformin when the animals were fed a low fat diet and exhibited no metabolic dysfunction (10,11).…”
Section: Introductionsupporting
confidence: 55%
See 2 more Smart Citations
“…Epidemiological studies consistently suggest an anti-cancer effect of metformin in individuals with diabetes, including breast cancer (1-3). A number of preclinical studies of mammary carcinogenesis and in vitro studies using breast cancer cell lines are consistent with this assertion of metformin's beneficial effects (4-9). Even so, other preclinical studies of mammary carcinogenic models failed to see any effect of metformin when the animals were fed a low fat diet and exhibited no metabolic dysfunction (10,11).…”
Section: Introductionsupporting
confidence: 55%
“…Numerous preclinical in vivo (4,6,12,27,28) and in vitro (5,7-9,14,29) cancer models have provided evidence of metformin's anti-tumorigenic potential, which is commonly attributed to indirect whole-body effects (insulin-dependent) and/or direct (insulin-independent) effects (30). Metformin has been shown to reduce hyperinsulinemia and glycemia thereby reducing tumor cell insulin receptor (IR) expression and downstream signaling (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study revealed that CD155 knockdown significantly weakened TGF‐β expression, indicating that CD155 also cross‐talked with TGF‐β signaling. In TNBC, TGF‐β was shown to induce EMT and metastasis . Smad family members such as Smad2, Smad3 and Smad4 mediated these processes .…”
Section: Discussionmentioning
confidence: 99%
“…For example, cell death mediated by metformin is autophagy mediated in particular cells of colon, melanoma and lymphoma cancers [286]. On the other hand, apoptosis is often observed with metformin treatment in breast, prostate, lung and head and neck cancers mediated by AMPK activation and p38 MAPK pathway [310]. One of the mechanisms for cell survival preference includes the cell's sensitivity to tumournecrosis-factor-related-apoptosis-inducing-ligand [212] induced apoptosis.…”
Section: Metformin and Apoptosis/autophagymentioning
confidence: 99%